Optimizing Village Economic Potential: A Sustainable Development Framework for Rural Areas in Bantan Subdistrict, Bengkalis Regency - ., Taryono; Iyan, Rita Yani; Sari, Lapeti (Journal of Ecohumanism, 2024)
This study explores a novel framework for optimizing village economic potential, emphasizing sustainability in Bantan Subdistrict, Bengkalis Regency. Utilizing a unique dataset from the Village Potential Survey (PODES) combined with in-depth interviews, the research identifies tourism, agriculture, and cultural heritage as key economic drivers. A detailed analysis highlights opportunities and challenges in leveraging coastal and peatland resources, particularly concerning infrastructure gaps and market isolation. The findings propose a collaborative model involving governments, communities, and private sectors to foster rural economic growth while ensuring environmental sustainability. The study’s interdisciplinary approach contributes to existing literature by offering localized strategies tailored to the socio-economic and ecological characteristics of rural areas.